2021
DOI: 10.1002/pon.5712
|View full text |Cite
|
Sign up to set email alerts
|

Symptom experiences in advanced cancer: Relationships to acceptance and commitment therapy constructs

Abstract: Objective This study examined relations between acceptance and commitment therapy (ACT) constructs and symptom‐based subgroups of advanced cancer patients. Methods Patients with advanced breast, gastrointestinal, lung, and prostate cancer (N = 201) completed questionnaires assessing five common symptoms and ACT variables (i.e., psychological inflexibility, cognitive fusion, values obstruction and progress, peaceful acceptance, mindfulness, and activity engagement) on one occasion. Results Latent profile analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…The ability to mitigate, if only partially, such negative total pain experiences allows patients to lower their stress levels and improve their ability to manage illness-related situations, which in turn will improve their capacity to adjust to their illness. This interpretation is supported by Mosher et al’s [ 39 ] study, which found that more activities directed at overcoming the negative consequences of cancer and the acceptance of cancer were associated with fewer symptoms of pain.…”
Section: Discussionmentioning
confidence: 58%
“…The ability to mitigate, if only partially, such negative total pain experiences allows patients to lower their stress levels and improve their ability to manage illness-related situations, which in turn will improve their capacity to adjust to their illness. This interpretation is supported by Mosher et al’s [ 39 ] study, which found that more activities directed at overcoming the negative consequences of cancer and the acceptance of cancer were associated with fewer symptoms of pain.…”
Section: Discussionmentioning
confidence: 58%
“…The majority of articles examined Acceptance and Commitment Therapy for patients (n = 15; 58%). 16,[47][48][49][50][52][53][54]57,58,60,65,67,69 Of these, 10 papers were focused on people with advanced cancer. 16,47,49,50,[52][53][54]57,58,60 Four were focused on Acceptance and Commitment Therapy for families or caregivers 62,63,66,68 , two a mix of both patients and caregivers.…”
Section: Study Populationsmentioning
confidence: 99%
“…16,[47][48][49][50][52][53][54]57,58,60,65,67,69 Of these, 10 papers were focused on people with advanced cancer. 16,47,49,50,[52][53][54]57,58,60 Four were focused on Acceptance and Commitment Therapy for families or caregivers 62,63,66,68 , two a mix of both patients and caregivers. 48,55 Three were focused on staff 45,56,61 and a further three involved people who had been bereaved.…”
Section: Study Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychological flexibility plays an important role in circumstances, such as advanced cancer, over which one can exert little or no control (Davis et al, 2017). It is associated with psychological and physical symptoms and QoL in people with advanced cancer (Mosher et al, 2017(Mosher et al, , 2021Novakov, 2021). Thus, given its aim of psychological flexibility, Acceptance and Commitment Therapy may be particularly well-suited for people with advanced cancer as it normalizes their distressing experiences and addresses existential concerns such as the loss of meaning and purpose by encouraging them to live in the present and engage in meaningful activities, thereby alleviating their psychological and physical symptoms (Moreno et al, 2022;Vehling et al, 2019).…”
Section: Introductionmentioning
confidence: 99%